Workplace learning and task performance: the moderating role of innovation and communication oriented culture - Daryoush, Younes; Hassanzadeh, Maryam; Silong, Abu Daud; Omar, Zoharah (International Journal of Current Research, 2016)
The Malaysian Public Service has taken diverse measures to reduce performance-related problems. The New Economic Model (NEM) was established in 2010 to strengthen the public sector in Malaysia in decision making and performance appraisal as well. It enhanced public sector performance and efficiency in service delivery and service quality. The purpose of this research was to investigate the strength level of the relationship between types of workplace learning and task performance in an innovation and communication-oriented culture. The relationship between three types of workplace learning, organizational culture and task performance were hypothesized to determine the moderating effect of communication and innovation orientation. These five hypotheses were supported. Interaction effect software was used to determine the power of relationship in the levels of a communication and innovation- oriented culture. The complementary role of these values was identified in the relationship between workplace learning and task performance.